If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -13 = 2x + 25 Reorder the terms: -13 + 4x = 2x + 25 Reorder the terms: -13 + 4x = 25 + 2x Solving -13 + 4x = 25 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -13 + 4x + -2x = 25 + 2x + -2x Combine like terms: 4x + -2x = 2x -13 + 2x = 25 + 2x + -2x Combine like terms: 2x + -2x = 0 -13 + 2x = 25 + 0 -13 + 2x = 25 Add '13' to each side of the equation. -13 + 13 + 2x = 25 + 13 Combine like terms: -13 + 13 = 0 0 + 2x = 25 + 13 2x = 25 + 13 Combine like terms: 25 + 13 = 38 2x = 38 Divide each side by '2'. x = 19 Simplifying x = 19
| 3/4x+8=14 | | (x+2)(x+2)=13 | | 0.24-0.03(x+3)=-0.03(1-x) | | 1/2t-3=7 | | 0.15/45 | | x+7x+4x= | | 8[1-(-4x-9)]=64x+152 | | ln(x^4)-ln(x^2)=3 | | 17+3*2-56/7 | | 3x-3=6x+3-3xt | | 3-3b=-3 | | 1/5+2/3z=1/3-3/4z | | 51-11x=15-7x | | -2n^2+13=0 | | (7x-12)+(5x+6)=90 | | 5x+7-2x=32-2x | | 18-r=14 | | 4(3n+4)=6(8n+1)+1 | | 12+17= | | -4(3+5m)-7=-38-m | | x-2/3=x/12+5/4 | | u-6/-2=-2 | | 2x+-2=6+4x | | 7x+53=3x+21 | | 8[1(-4x-9)]=64x+152 | | 2/3(3-x)=1/6(x-3) | | 6-2(2w+1)=12w-2(12+w) | | 3.5x-0.2=10.3 | | 4x-12=-13 | | m+12/9m=6/9 | | 6x-12x=-48 | | -4/9p=8/21 |